BEYOND THE PROHIBITION OF LKS IN INDONESIA: A REVIEW ON ENGLISH LKS USED IN ELEMENTARY SCHOOL - Naja, Emmi (Lingua Scientia, 2016)
The LKS (Lembar Kerja Siswa) usage has been criticized by educational experts in the latest decade, including in Indonesia.Publishing permendikbud no 8 tahun 2016 that administered both textbook and non-textbook used in Indonesian schools becomes government respond to this issue. This present article tries to fnd facts that contradict to those rules by reviewing 8 English LKS for Elementary Students. Moreover, some theoretical controversies also fnd in those LKS such as grammatical errors, ignoring young learnersâ characteristics, and less of enjoyable activities for young learners. So, this review results are supported to government decision in banning LKS usage in Indonesia.